Zasada incompatibilitas w samorządowym prawie ustrojowym (relacje samorządowiec-parlamentarzysta) i projekt przekształcenia Senatu w Izbę Samorządową - Łukaszewski, Marcin (Wydawnictwo Naukowe WNPiD UAM, Poznań, 2011)
The problem of senate as a self-government chamber and self-government person – parliament deputy relations were shown in the political history of the Polish Third Republic many times. In 2001, when self-government laws were introduced into the political system of selfgovernment, there was an institution of incompatibilitas (incompatibility of self-governmental and parliamentarian seats). It influenced the subsequent public debate about the role of Senate and the emerging plans to transform it into a self-government chamber.

Problem Senatu jako izby samorządowej i wzajemnych relacji samorządowiec-parlamentarzysta pojawiał się w historii III RP wiele razy. W 2001 roku, kiedy to znowelizowano samorządowe ustawy ustrojowe, wprowadzono do samorządowego systemu politycznego instytucję incompatibilitas w łączeniu mandatów samorządowca i parlamentarzysty. Zakaz ten znacząco wpłynął na późniejszą debatę publiczną nad rolą Senatu i pojawiającymi się planami przekształcenia tego organu w izbę samorządową.
The Incompatibilitas Rule in Self-Government Constitutional Law and the Project of Transforming Senate Into Self-Government Chamber
Keywords: incompatibilitas; prawo wyborcze; senat; samorząd